2022
DOI: 10.2147/ppa.s354181
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Depressive Symptoms on the Association Between Neighborhood Social Cohesion and Quality of Life in Individuals with Type 2 Diabetes Mellitus

Abstract: Purpose Few studies have explored the association between neighborhood social cohesion (NSC), a type of social capital, and the quality of life of patients with type 2 diabetes mellitus (T2DM). In addition, the potential mechanism for this association remains unclear. The current study examined the mediation effect of depressive symptoms on the relationship between NSC and quality of life among diabetes patients in China. Patients and Methods A cross-sectional study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Our findings indicate that NSC is a significant predictor of life satisfaction among T2DM patients (β = 0.03, p < 0.001), aligning with previous research suggesting that enhancing well-being and life satisfaction can be achieved through NSC or social capital (35,36). Moreover, a previous study has demonstrated a positive correlation between high levels of NSC and improved quality of life in T2DM patients (16). Additionally, our study reveals a negative association between depressive symptoms and life satisfaction (β = −0.01, p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings indicate that NSC is a significant predictor of life satisfaction among T2DM patients (β = 0.03, p < 0.001), aligning with previous research suggesting that enhancing well-being and life satisfaction can be achieved through NSC or social capital (35,36). Moreover, a previous study has demonstrated a positive correlation between high levels of NSC and improved quality of life in T2DM patients (16). Additionally, our study reveals a negative association between depressive symptoms and life satisfaction (β = −0.01, p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…(18). Our previous study indicated a strong correlation between NSC and depressive symptoms in T2DM patients (16). Worth noting, depressive symptoms were highly associated with life satisfaction in a nationwide sample of healthy Finnish adults (N = 9,679) (19), but not reported in diabetes patients.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our data provide further support of a mediating effect of the BMI and HRQOL on the association between diabetes and depressive symptoms. But it must be considered that there may be a chicken-egg problem with HRQOL and depressive symptoms, because depressive symptoms can also be considered as a mediator between diabetes and HRQOL [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%